Roles of youth towards agricultural practice in Malaysia - Arif Shah, Jasmin; Asmuni, Azizan; Ismail, Azahari (Institute for Social Science Studies, Universiti Putra Malaysia, 2013)
Nowadays, agriculture becomes a very important field in our country. It is expected that the income generated by agricultural industry will increase year by year. In order to achieve this, extension agents especially young generation plays important roles in educating farmers by encouraging them to learn, adopt new technologies and spread them to other farmers. To ensure the success of extension program, the agents should recognize their roles as change agents (as a catalyst, solution giver, process helper, and resource linker) and have ability to acquire competencies to accomplish these roles. Thus, this study aims to explore the level of roles among youth as extension agents. This study uses a quantitative survey methodology and self-administered questionnaires. A total of 92 young extension agents had participated. Farmers, policy makers, researchers, academics and people working in agriculture can learn a great deal about what individuals and institutions need to do to develop farmers, personally and professionally.